1988
DOI: 10.1002/jsfa.2740440110
|View full text |Cite
|
Sign up to set email alerts
|

Free‐choice flavour and odour profiling of fish spoilage: Does it achieve its objective?

Abstract: A BS T R A C TFree-choice odour and flavour profiling of fish spoiling under diflerent regimes leads to a wide range of descriptors which are difjicult to collate and quantify. An attempt was made to gain an insight into the spoilage process by applying a variety of analytical techniques to the profile data including cluster analysis, principal coordinates analysis and especially generalised Procrustes analysis. However, it was concluded that manipulation of 9 e echoice profiles does not provide any additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…I t has been shown, however, by Wilson & Lindsay (1969), and discussed by Quarmby & Ratkowsky (1972), that the relationship between solids* or dry matter* and SG in vegetative tissue, is only near-linear and the true linear relationship lies between DM and the reciprocal of SG or specific volume (SV).…”
Section: A R Quarmbymentioning
confidence: 94%
See 3 more Smart Citations
“…I t has been shown, however, by Wilson & Lindsay (1969), and discussed by Quarmby & Ratkowsky (1972), that the relationship between solids* or dry matter* and SG in vegetative tissue, is only near-linear and the true linear relationship lies between DM and the reciprocal of SG or specific volume (SV).…”
Section: A R Quarmbymentioning
confidence: 94%
“…All experimental work was carried out at constant temperature (20°C), and weighings in air and water were made on a top pan balance reading to 10 mg. Before use, all weight data were corrected for air buoyancy. , 1969;Quarmby & Ratkowsky, 1972) then And so if the first part of the intratuber DM concentration gradient is considered linear (profile A, Fig. 2), then the first part of the SGI gradient must be non-linear (profile B, Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique has been applied to fish products by several workers at the Seafood Technology group of the CSIRO. Quarmby and Ratkowsky (1988) used the method to evaluate the process of fish spoilage in a comparison of the use of onboard handling of gemfish. Analysis of the terms chosen by each assessor showed that the first principal component was essentially an acceptability axis as the descriptors showed association with spoiled fish odours.…”
Section: Developments In Descriptive Analysismentioning
confidence: 99%